2017
DOI: 10.1111/jphp.12726
|View full text |Cite
|
Sign up to set email alerts
|

Immunotropic aspect of the Bacillus coagulans probiotic action

Abstract: According to all parameters, B. coagulans has been proved to be more effective as compared to the Linex Forte reference product containing lacto- and bifidobacteria.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…B. coagulans as a spore forming bacterium is one of the most promising probiotic bacteria, but still some of its pharmacological aspects have not been clarified yet (7). This bacterium can tolerate the acidic conditions of the stomach until it reaches the intestine and germinates there.…”
Section: Introductionmentioning
confidence: 99%
“…B. coagulans as a spore forming bacterium is one of the most promising probiotic bacteria, but still some of its pharmacological aspects have not been clarified yet (7). This bacterium can tolerate the acidic conditions of the stomach until it reaches the intestine and germinates there.…”
Section: Introductionmentioning
confidence: 99%
“…Oral supplementation with A. muciniphila after FMT with nonresponder feces restored the efficacy of PD-1 blockade (Routy et al, 2018). Bacillus coagulans were proved to improve chronic colitis, enhance immunity, inhibit enteropathogenic bacteria, and repair the intestinal mucosa (Bomko et al, 2017). The treatment with Bacillus coagulans and the prebiotic inulin significantly inhibits serum amyloid A protein in arthritic rats and promotes a significant TNF release decrease (de Oliveira, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the study of S. Zhao et al Bacillus coagulans 13002 can promote the recovery of serum immune protein and immune factor levels in immunosuppressed mice fed cyclophosphamide (Zhao et al 2021). It has also been reported in the literature that mice that ingested streptomycin with cyclophosphamide to suppress organism immunity caused intestinal dysfunction, and the data showed that Bacillus coagulans had a significant ameliorating effect, with a 75% decrease in diarrheal symptoms and a return to normal gastrointestinal function, which was better than the ingestion of products containing Lactobacilli and Bifidobacteria (Bomko et al 2017). Furthermore, Bacillus coagulans also plays a regulatory role in promoting the body to revive health in chronic immune diseases.…”
Section: The Immune Regulationmentioning
confidence: 96%